A Clinical Trial of Voriconazole for Deep-seated Mycosis: An Uncontrolled Multicenter Study - Niki, Yoshihito (Japanese Journal of Chemotherapy, 2005)
This was an uncontrolled multicenter study to assess the clinical usefulness (efficacy and safety) of voxiconazole (VRCZ) for deep-seated mycosis. Efficacy was assessed in 65 of 100 subjects given the study drug, while safety was assessed in 100 subjects. For oral therapy, 300 mg of VRCZ was administered twice as the loading dose on Day 1, and patients then received 150-200mg twice daily on subsequent treatment days. For intravenous therapy, 6 mg/kg of VRCZ was administered twice as the loading dose on Day 1, and the maintenance dose for subsequent treatment days was 3mg/kg twice daily or in the case of severe mycosis, 4 mg/kg twice a day. When plasma VRCZ concentrations were equal to or greater than 2.5 μg/mL on Day 3 of oral and intravenous administration, dosages were decreased on Days 5-7. A switch from intravenous to oral formulation (switch therapy) was allowed after intravenous therapy had been given for at least 3 days. Treatment lasted 12 weeks. Global efficacy was 68.3%(28/41) for aspergillosis, 91.7%(11/12) for candidiasis, and 100%(8/8) for cryptococcosis. Global efficacy for primary therapy was 91.2%(31/34) and that for salvage therapy 61.3%(19/31). Eradication in the 65 cases evaluated for efficacy was 69.2%(9/13) for Aspergillus spp. and 91.7%(11/12) for Candida spp. Treatment-related adverse events were reported in 78 of 100 cases. The most common adverse events were photophobia (25.0%), visual disturbance (24.0%), vomiting (8.0%), hepatic function abnormalities (8.0%), headache (8.0%), and increased γ-GTP (7.0%). Vision-related adverse events were transient and reversible in all cases. Most treatment-related adverse events were mild to moderate in severity. No relationship was seen between plasma VRCZ concentrations and either the efficacy or safety of this drug. These results indicate that VRCZ is useful for the treatment of severe or intractable deep-seated mycosis.